Amblesan di daerah Porong, Kabupaten Sidoarjo, Jawa Timur - Untung Sudarsono; Indra Budi Sudjarwo (Geological Agency, 2008)
http://dx.doi.org/10.17014/ijog.vol3no1.20081On 29th May 2006, there was a huge mud outpouring in the Porong Subregency, Regency of Sidoarjo, East Jawa and for one year, it had flooded the area of more than 5 km2 including Porong, Tanggulangin and Jabon Sub-regencies. The mud known as Lumpur Sidoarjo. The impact of the mud outpouring was the presence of a subsidence around the main outpouring for the width of 6.3 km2 in ellipse stretching to the north. The subsidence area covered Tanggulangin Sub-regency: Kedungbendo Village, Porong Sub-regency: Siring, Jatirejo, Mindi, and Renokenongo Villages, and Jabon Sub-regency: Pejarakan and Besuki Villages. The rate of the subsidence is ap- proximately 2 cm/day.